Pengujian Keandalan Sistem Current Transformer Dalam Menanggulangi Penggunaan Energi Listrik Secara Ilegal - Moranain Mungkin; Habib Satria; Zulkifli Bahri; Ahmad Ridwan (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2020)
The increasing demand for and tariffs on electricity has made people choose to take the risk of going against the law by illegally stealing currents on state-owned electricity networks. This is very detrimental if there is an electrical short circuit which can cause a fire. Therefore, a physical detection method is needed, namely by directly checking the seal meter and supported by a tool to prevent the occurrence of illegal use of current which is effective so that the measurement directly to the consumer can obtain valid data results. The tool used to overcome the problem of rampant illegal current theft is to install a current transformer (CT) on the kWh meter. Simulations are carried out at the electrical measurement laboratory of the Medan Area University electrical engineering study program by testing the reliability of the current transformer. The test results show that the data on the use of legal load currents and illegal load currents after the installation of current transformers, there is an increase in power where after using the CT the detected power consumption is 426 W, previously the power was fixed at 306 W, using both legal and illegal currents. The research found that simple installation using current transformers is very helpful for PLN in preventing the use of illegal electricity without having to routinely check consumers. Utilization of CT applications can also reduce the occurrence of leakage currents and short circuits in illegal use of electric current.